THE PORTRAYAL OF MULTIPLE INTELLIGENCES-BASED INSTRUCTION::A Case Study of English for Young Learners Class at Mutiara Hati ElementarySchool - Euis Komariah, - (2008)
This present study entitled "The Portrayal of Multiple Intelligences-based Instruction* ACase Study ofEnglish for Young Learners Class at Mutiara Hati Elementary School". This study examines the use of multiple intelligences-based instruction in EFL for young learners. The aims of the study are to investigate the implementation of multiple intelligences and the barriers faced by the teacher. The data were obtained from video recordings and interviews. The data were transcribed and coded, then they were analyzed using multiple intelligences theory proposed by Gardner (1999) and Armstrong (2002). The findings of the study show that the teacher under investigation did employ strategies of multiple intelligences within her instruction. The strategies are brainstorming, calculations and quantifications, classifications and categorizations, socratic questioning, visualization, picture metaphors, kinesthetic concept, body maps, songs, peer sharing, cooperatives groups, one-minute reflection periods, personal connections, and travelling. In addition, the combinations of multiple intelligences are also found. Meanwhile, the barriers faced by the teacher were the description of teaching strategies, classroom condition and students' psychological condition. This study concludes that teachers in young learners' foreign language classroom can be the exposure provider. Asystematic and well prepared design of language instruction can facilitate students to enhance their proficiency by providing a great exposure. And competent teachers may support a better and comprehensible language instruction.